1993
DOI: 10.4319/lo.1993.38.6.1101
|View full text |Cite
|
Sign up to set email alerts
|

Transport dynamics of fine particulate organic matter in two Idaho streams

Abstract: Natural suspended fine particulate organic matter (FPOM, was labeled with 14C and reinjected to estimate transport distances in the water column and retention times within the sediments of two Idaho streams. Transport of labeled FPOM particles declined exponentially with downstream distance. yielding mean transport distances of 800 and 580 m in Smiley Creek in 1989 and 1990 at a mean water velocity of 0.27 m ss' and mean depth of 0.34 m in both years, and a distance of 630 m in the upper Salmon River at a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
177
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(191 citation statements)
references
References 15 publications
9
177
5
Order By: Relevance
“…This observation diverges from many previous findings on particle transport that showed a strong positive relationship among hydrological predictors (i.e., discharge, flow velocity, shear stress) and transported PM (Maciolek 1966;Naiman & Sedell 1979;Wilcox et al 2008). Besides water column/near-bed hydrological conditions, particle transport in streams is greatly affected by initial benthic material distribution, substratum and channel (geo)morphology, complexity of in-stream retention structures, and biological activity (Cushing et al 1993;Cordova et al 2008;Small et al 2008). It appears that the crucial control mechanism of the in-stream transport capacity is the stream's ability for material retention and resuspension.…”
Section: Patterns Of Particulate Matter Transportcontrasting
confidence: 55%
“…This observation diverges from many previous findings on particle transport that showed a strong positive relationship among hydrological predictors (i.e., discharge, flow velocity, shear stress) and transported PM (Maciolek 1966;Naiman & Sedell 1979;Wilcox et al 2008). Besides water column/near-bed hydrological conditions, particle transport in streams is greatly affected by initial benthic material distribution, substratum and channel (geo)morphology, complexity of in-stream retention structures, and biological activity (Cushing et al 1993;Cordova et al 2008;Small et al 2008). It appears that the crucial control mechanism of the in-stream transport capacity is the stream's ability for material retention and resuspension.…”
Section: Patterns Of Particulate Matter Transportcontrasting
confidence: 55%
“…This approach, however, implicitly assumes that benthic POM in streams and rivers consists of a well-mixed pool that continually and thoroughly exchanges with the overlying suspended POM, and does not address the questions of how frequently exchanges occur and whether the exchange involves the entire stock of benthic POM. Tracer additions of 14 C-labeled natural seston (Cushing et al 1993;Minshall et al 2000) and of surrogates such as spores (Wanner and Pusch 2000), corn pollen (Georgian et al 2003), bacteria (Hall et al 1996), and yeast (Paul and Hall 2002) have shown that there is a rapid and continual deposition of fine particles onto the streambed. The delivery of particles to the bed appears to be governed more by turbulence than by gravitational settling (Hall et al 1996;McNair et al 1997;Thomas et al 2001).…”
mentioning
confidence: 99%
“…The ''turnover length'' for a form of organic carbon, or the downstream distance it travels until it is mineralized, can be represented as the product of its biological turnover time and downstream velocity (Newbold et al 1982;Webster et al 1999). Organic particles move downstream as a series of saltations interspersed by stationary periods in the streambed (Cushing et al 1993;Webster et al 1999), so that they migrate downstream at a velocity far slower than that of the Values are averages for the reach unless otherwise stated. From Minshall et al (2000).…”
mentioning
confidence: 99%
“…Recently, studies of POM transport and deposition have been conducted using experimental additions of radioactively labeled natural detritus (Cushing et al 1993;Minshall et al 2000;Thomas et al in press), seston analogs (Miller and Georgian 1992;Webster et al 1999), and fluorescently labeled bacteria (Hall et al 1996). Cushing et al (1993) and Minshall et al (2000) observed total instream loss rates ranging from 0.15 to 17.14% per longitudinal meter for POM between 52 and 106 m in size. These values are equivalent to downstream transport distances, S P , of 5.8-667 m, where S P equals the inverse of the longitudinal loss rate (S P ϭ 1/k P ).…”
mentioning
confidence: 99%